INTERRELATIONSHIP BETWEEN THE FORMATION OF LOCAL BUDGET REVENUES WITH THE ECONOMIC AND INVESTMENT CAPACITY OF REGIONS (American Journal of Business Management, Economics and Banking, 2025)
This article analyzes the relationship between the process of local budget revenue formation and the economic and investment potential of regions. The impact of regional economic activity, the level of investment attraction, and local production capabilities on budget revenues is shown. Also, differences in revenue formation across regions and their causes are studied, and practical proposals are developed to expand the budget revenue base by improving the investment climate.